Solving Economic Dispatch Problem with Valve-Point Loading Effects and Network Constraints Through Gradient-Based Approach - Pinheiro, Ricardo B. N. M. [UNESP]; Nepomuceno, Leonardo [UNESP]; Tsuzuki, MDG; Junqueira, F. (Ieee, 2018)
The Economic Dispatch Problem with Valve-Point Loading Effects and AC Network Constraints (EDP-VPE-AC) is defined as a nonsmooth and nonconvex optimization problem. Due to nonsmothness of cost function, the gradient-based approaches can not be used directly for solving it. In this paper, we present an alternative formulation for EDP-VPE-AC that allow us solving it by means of gradient-based approaches. We provide numerical results involving the IEEE power systems with 14 and 30 buses, which are obtained by application of a primal-dual logarithmic modified barrier function type approach.
Keywords: Power Systems; Optimal Power Flow; Economic Dispatch Problem with Valve-Point Loading Effects; Logarithmic Modified Barrier Function Methods